2019
DOI: 10.21101/cejph.a5514
|View full text |Cite
|
Sign up to set email alerts
|

Immunization related behaviour among healthcare workers in Europe: Results of the HProImmune survey

Abstract: Objectives: Vaccine preventable diseases (VPDs) continue to pose a significant threat to healthcare workers (HCWs) while immunization among this group remains low. HCWs' behaviours as well as facilitators and barriers towards their vaccination for a number of VPDs were explored through an EU-wide survey. Methods: HCWs across the EU answered online survey that explored attitudes and behaviours towards vaccination for a number of VPDs. Response data were adjusted based on weights estimated by HCWs' country and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
1
27
0
3
Order By: Relevance
“…A recent study involving 14 European countries found an overall of 65.7% HCWs favouring mandatory immunisation for HCWs involved in clinical work. However, rates differed significantly among countries [28] . Interestingly, when asking the public, >90% agree that HCWs have an obligation to be vaccinated against influenza and pertussis and just as many support vaccination for childcare workers [29] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study involving 14 European countries found an overall of 65.7% HCWs favouring mandatory immunisation for HCWs involved in clinical work. However, rates differed significantly among countries [28] . Interestingly, when asking the public, >90% agree that HCWs have an obligation to be vaccinated against influenza and pertussis and just as many support vaccination for childcare workers [29] .…”
Section: Discussionmentioning
confidence: 89%
“…Several ethical issues are associated with HCW immunisation and mandatory vaccination is far from Danish principles. A voluntary vaccination program seems the best approach to foster greater employee cooperation and trust in the system [28] . Education regarding the potential health consequences for patients, diagnosis, treatment, modes of transmission and easy access to free vaccines including worksite vaccination during all shifts will undoubtedly increase vaccination uptake and must be prioritised before considering mandatory programs.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends that HCP should be vaccinated against influenza each year and free SIV has been provided to HCP in many locations [12,13]. However, despite great efforts on promoting SIV among HCP, uptake rates remain unsatisfactory in the US [14], and widespread low in most European countries [15,16], Australia [17] and also in Hong Kong [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…At the European level, Slovenian and Italian HCWs resulted to be the most skeptical professionals with regards to vaccination [9]. The discussion of our results with the surveyed healthcare institutions allowed all participants to compare strategies adopted, while indirectly increasing awareness about HCWs' vaccination crucial role.…”
Section: Discussionmentioning
confidence: 80%
“…Global and national data about HCWs vaccine coverage are not satisfying, as in Italy just 65% of HCWs are vaccinated for varicella, 80.5% for measles-mumps-rubella (MMR), and 93.7% for pertussis [6]; moreover, influenza vaccine coverage among HCWs is even worse [6,7] still being far from reaching desired levels. Even if strongly recommended by the scientific community [5,8] and not largely opposed by HCWs [9,10], as long as HCWs vaccination is not mandatory, great importance should be given to vaccination campaign rendering within healthcare organizations [7]. This study aims at describing HCWs vaccination campaign design within healthcare institutions of a North Italian Region (Friuli Venezia Giulia Region), comparing different strategies also considering healthcare institutions' characteristics and influenza vaccination coverage for 2019-2020 season.…”
Section: Introductionmentioning
confidence: 99%